Studi validasi indeks massa tubuh dan rasio lingkar pinggang panggul terhadap profil lipid pada pasien rawat jalan di Poli Jantung RSUP Dr. Sardjito Yogyakarta - Tenta Septiana; Martalena Purba; Yayuk Hartriyanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Obesity is one of nutrition status categories that can be measured with various methods, just like nutrition status. So far, anthropometric methods such as body mass index (BMI) and Waist-to-Hip Ratio (WHR) are commonly used due to their practicality and inexpensiveness. However, biochemical examination will give more objective result, apart from its ability to make early detection of body changes. Lipid profie is a biochemical method that can be used to predict excess of fat deposit (hyperlipidemia) that causes obesity.Objective: To identify validity of BMI and WHR compared to lipid profie of out-patient at cardiology clinic of Dr. Sardjito Hospital.Method: The study was observational with cross sectional design undertaken at cardiology clinic of Dr. Sardjito Hospital Yogyakarta. Samples were patients of over 40 years old that had blood lipid profie whose height, weight, waist and hip circumference could be measured and were willing to participate. Patients on wheel chair or unable to stand up properly and wearing tight clothes were excluded. Sensitivity and specifiity test was made to assess the validity of BMI and WHR against lipid profile. Result: As many as 52 samples (53.6%) had hypercholesterolimia, 45 (46.4%) had normocholesterolemia. As many as 38 samples (39.2%) had hypertrygliceridemia, 59 (60.8%) had normotrygliceridemia. Based on BMI 76 samples (78.3%) were obese and 21 (21.7%) non obese. Based on WHR as many as 79 samples (81.5%) were of central obese and 18 (18.5%) non obese. Sensitivity of BMI and WHR was good but their specifiity was low.Conclusion: BMI and WHR could be used to detect hypercholesterolemia and hypertrygliceridemia due to their good sensitivity; but they could not be used to predict normocholesterolemia and normotrygliceridemia due to their low specificity.